2012
DOI: 10.1007/s10565-012-9214-1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse action of acrylamide on cytochrome P450 and glutathione S-transferase isozyme activities, mRNA levels and protein levels in human hepatocarcinoma cells

Abstract: Humans are exposed to acrylamide in their diet and cigarette smoke. Acrylamide is metabolized into glycidamide by CYP2E1. However, very few studies regarding the effects of acrylamide on cytochrome P450 and Glutathione S-Transferase (GST) isozymes have been pursued. The aim of this study is to elucidate the effects of acrylamide on cytochrome P450 and GST isozymes in HepG2 cell line. Treatment with 1.25 and 2.5 mM acrylamide caused 9.5- and 3.7-fold increases and 4.0- and 3.3-fold increases in CYP1A-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 65 publications
0
20
2
1
Order By: Relevance
“…A recent study by Sen et al, (2012) showed AC induced EROD and MROD activities in HepG2 cells, however AC did not affect EROD in MCL-5 cells in the current study, nor was there any effect on BaP-induced EROD activity. However, it should be noted that this was following a 24h treatment in our study, whereas Sen et al (2012) used a 48h treatment. These results suggest that an alternative mechanism to one involving modulation of CYP2E1 activity is involved in the synergistic interaction, but more investigation is required to elucidate this.…”
Section: Mutagenicity Of Individual Chemicalscontrasting
confidence: 91%
See 1 more Smart Citation
“…A recent study by Sen et al, (2012) showed AC induced EROD and MROD activities in HepG2 cells, however AC did not affect EROD in MCL-5 cells in the current study, nor was there any effect on BaP-induced EROD activity. However, it should be noted that this was following a 24h treatment in our study, whereas Sen et al (2012) used a 48h treatment. These results suggest that an alternative mechanism to one involving modulation of CYP2E1 activity is involved in the synergistic interaction, but more investigation is required to elucidate this.…”
Section: Mutagenicity Of Individual Chemicalscontrasting
confidence: 91%
“…While AC does require metabolic activation, this occurs via CYP2E1, and as such is not expected to be influenced by BaP. A recent study by Sen et al, (2012) showed AC induced EROD and MROD activities in HepG2 cells, however AC did not affect EROD in MCL-5 cells in the current study, nor was there any effect on BaP-induced EROD activity. However, it should be noted that this was following a 24h treatment in our study, whereas Sen et al (2012) used a 48h treatment.…”
Section: Mutagenicity Of Individual Chemicalscontrasting
confidence: 59%
“…Conjugation of acrylamide with GSH can result in depletion of cellular GSH stores, leading to altered gene expression directly or through regulating various redox-dependent transcription factors [7]. Considering the fact that acrylamide induces GST activity [25, 26], it would be expected that the positive association between acrylamide and ovarian cancer is only present among women with at least one copy of the genes in whom the activity of GST can be induced.…”
Section: Discussionmentioning
confidence: 99%
“…In order to study whether AA itself could induce CYPs, cultured human HepG2 cells, which are derived from a hepatic adenocarcinoma, were treated with 1.25 and 2.5 mM AA (Sen et al, 2012). A 2.0-2.6-fold, 2.4-3.2-fold, and 1.4-1.9-fold increase in CYP2E1-associated enzyme activity, protein level and m-RNA level, respectively, was observed.…”
Section: Enzymes For Metabolic Activationmentioning
confidence: 99%
“…Data on the induction of GSTs by AA are also very rare. Sen et al (2012) studied the effects of AA at 1.25 mM and 2.5 mM concentration on the activity and expression of GST-mu and GST-pi isozymes in cultured HepG2 cell. A slight induction (2.0-5.1-fold, depending on the endpoint) was observed for GST-mu, whereas the activity and expression of GST-pi were reduced.…”
Section: Enzymes For Metabolic Inactivationmentioning
confidence: 99%